A study on the construction of destination image for China’s county-level integrated media centers: a case study of four counties in Fuzhou - Lin, Hanzheng; Wen, Hongyan; Ma, Zhuokai (Frontiers in Communication, 2024)
Today, as social media plays an increasingly important role in disseminating destination images, short videos have emerged as the primary channel through which tourists obtain information about their desired destinations. In comparison to traditional methods of using text and pictures, the new media accounts of local government agencies offer a means to convey more comprehensive local news and shape destination images that are more accurate and diverse, leveraging the potential of the short video platform. This study utilizes a combination of manual analysis (subject terms classification) and computer-assisted techniques (key-frame extraction and text mining) to examine the short videos posted on the TikTok (Douyin) platform by the integrated media centers of Minhou County, Yongtai County, Minqing County, and Lianjiang County in Fuzhou City, China. The objective is to explore the shared characteristics and variations in the dimensional aspects of destination images. The findings reveal that the short video contents released by the governmental new media accounts in these four locations primarily highlight three dimensions: stakeholders, urban infrastructures, and regional landscapes. These dimensions are evident in both descriptive texts and visual symbols.However, in terms of the presented destination image, a notable degree of homogeneity is observed, and there is a lack of emphasis on uncovering and presenting the cultural dimensions, thus failing to fully reflect the distinctive local characteristics.Consequently, it is essential for local integrated media centers to thoroughly explore the cultural uniqueness of their respective regions and enhance the development of thematic dimensions in creating short video content. This approach will effectively strengthen tourists' association with and perception of destination images.